Islamic banking service quality and withdrawal risk: the Indonesian experience - Abduh, Muhamad (Hamdan Bin Mohammed e-University (HBMeU), 2011)
This paper aims first to evaluate the service quality of Islamic banking and second to explore the withdrawal behavior of Islamic banking depositors based on their evaluation towards its service quality in the context of Indonesia. Islamic banking service quality. Next, we use central tendency measurement to extract the information of depositors’ withdrawal behavior towards those dimensions. Afterwards, the importance and performance analysis (IPA) was employed to evaluate the level of Indonesian Islamic banking service quality.